Penyuluhan Metode Isolasi Mikroba Jamur dan Bakteri pada Siswa Kelas X SMA Swasta Perguruan Advent 1 Medan - Raissa Fitri; Dumartina Hutauruk; Cinta Cornelia; Della Putri Anggraini; Bramsion Paskah Sitorus; Chintya Bella Sitohang; Dinda Delfia; Enjel Putri Sinaga; Ramayanti Ramayanti; Joice Harefa; Stefalin Raja Gukguk; Julfan Bulolo (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aims to improve students' knowledge regarding microbial isolation methods for fungi and bacteria, which form an important basis in the fields of microbiology and pharmacy. The problem encountered was the limited knowledge of high school students about basic microbiology concepts, particularly microbial isolation techniques, as this material has not been taught in depth at the secondary education level. The proposed solution was an interactive counseling session consisting of a presentation on microbial isolation methods (streak plate, pour plate, spread plate, serial dilution, and surface sterilization), followed by a rewarded question and answer session and a post-test to measure the improvement in students' understanding. The activity was carried out for Grade X students of SMA Swasta Perguruan Advent 1 Medan, totaling 32 students. The post-test results showed an improvement in students' understanding of microbial isolation material, with the percentage of correct answers increasing from 35% before the activity to 82% after the counseling session, as illustrated in a comparison chart. This activity is expected to foster students' interest in microbiology and pharmacy from an early stage.